THE EFFECT OF CIPROHEPTADINE ON SOME RISK FACTORS FOR COMORBID DISEASES - Ibadova M.U; Chernysh P.P (Scholar Express Journals, 2024)
The article analyzes the results of a study of the effect of cortisol on some hemodynamic and carbohydrate metabolism indices. A group of patients suffering from metabolic syndrome identified according to the IDF criteria (2005) was observed. At the time of the study, the patients were aged 40–59 years (mean age 54 years). Cyproheptadine was prescribed to reduce cortisol levels. The observation lasted 14 days. It was shown that against the background of cyproheptadine use, there is a decrease in the level of endogenous cortisol, blood pressure, glycemia, and immunoreactive insulin
Keywords: blood pressure; hyperglycemia; cortisol; insulin